Mark Brender: The Role of Partners in Health in Combatting the West African Ebola Epidemic - Sivarajah, Vishalini; Bhatnagar, Priyank; Cho, Hannah; Shin, Saeha (The Meducator, 2016)
Partners in Health (PIH) is a not for profit international organization committed to providing global health equity that was founded in 1987 by Paul Farmer, Thomas White and Todd McCormack in Boston, Massachusetts. Recently, PIH has taken a major role in combatting the Ebola epidemic. As members of the McMaster chapter of PIH, we recently had the opportunity to speak with with Mark Brender, the director of PIH Canada, about PIH’s role in West Africa.